The Effectiveness of the Use of Movement Games in the Early Training Phase of Young Handball Players - Berdiyeva Xurshida Karimova (International Journal on Integrated Education, 2021)
The material offered in this article explains how to mold the specific skills of young pupils in handball by using age-appropriate methods rather than their own workouts. The problem of targeting affects on the formation and development of coordination abilities in young learners, accurate stratification of spatial, temporal, and power aspects of movements, and feeling of rhythm can be solved using these techniques.